Detection of some virulence genes (Esal and OmpA) in Pantoea spp. isolated from different clinical specimens from patients referred to hospitals in Mosul (Iraq) - N. F. Al-Rawi; A. Al Nauman; F. H. Hussien (Regulatory Mechanisms in Biosystems, 2025)
Pantoea spp. (previously Enterobacter spp. and Erwinia spp.) are Gram negative aerobic or facultatively anaerobic bacilli in the family Erwiniaceae. They are opportunistic pathogens that cause different human infections. Our s tudy aims to investigate the existence of Pantoea spp. isolated from clinical specimens of patients in hospitals of Mosul city, study their antibiotic resistance and detect some virulence genes of these isolates. For the identification of Pantoea spp., we used Analytical Profile Index 20 (API 20) . E xtraction DNA from isolates w as subjected to 16S rRNA amplification by PCR. We detected the existence of factors responsible for pathogenesis ( E sa l , O mpA ) genes. The highest number of Pantoea spp. in clinical samples was found in wound swabs followed by urine and ear swabs, 5 .00 %, 1.88% and 1.33% respectively . Pantoea spp. infection prevalence was higher in male s than female s . The present study explained that Pantoea spp. were more sensitive to meropenem and cefotaxime than other antibiotics. The molecular diagnosis of all isolates ( f ourteen) w as confirmed by 16S rRNA. Seven isolates were studied for inve s tigation of virulence factors, results showed that 7/7 (100%) isolates contain ed the virulence genes ( E sal , O mpA ), which partic i pate to increase their pathogenicity. Pantoea spp. was isolated from different clinical specimens, so it may be the cause of various infections in human s . The PCR technique detected the existence of genes which are responsible for virulence ( E sal and omp A ), these genes are important in causing bacterial infections. Genetic variation was examined, show ing multiple mutation of (16S rRNA, E sal ) genes, and point mutation of the O mpA gene.